Health risk assessment of the workers exposed to the heavy metals in e-waste recycling sites of Chandigarh and Ludhiana, Punjab, India. (July 2018) - Singh, Manmohit; Thind, Parteek Singh; John, Siby
Abstract: Investigations were made to analyze the effects of heavy metals on the adults and children working in informal e-waste recycling sectors of Chandigarh and Ludhiana, Punjab, India. Soil samples of the ground where recycling was being done, dust from the platform where recycling activities were done and dermal samples of workers were collected to estimate the presence of heavy metals (As, Cu, Co, Cd, Cr, Ni, Fe, Zn, Pb, Ba) in them. High concentration of Ba, Cu, Pb and Zn was observed in the soil and dust samples. Cr, Pb and Zn were observed in high concentrations in dermal samples. These heavy metals could cause serious health effects. Therefore, human health risk assessment was also done using carcinogenic (cancer risk potency factor) and non-carcinogenic (health hazard index) health risk assessment. Carcinogenic hazards were not reported in children however, hazard index, for soil and dust contamination for some heavy metals, was found significant (Soil samples: As = 1.69, Cr = 1.38, Cu = 4.5 and Pb = 5.82 and dust samples: Pb = 2.97). Carcinogenic hazards were reported in adults from Cr contamination in soil samples (3.4E-03). Highlights: Sand, working platform dust and dermal samples of the workers analysed for the presence of heavy metals in the e-waste dismantling sites of Chandigarh and Ludhiana, Punjab, India. Ba, Cu, Pb and Zn were identified as major pollutants of in these e-waste dismantling sites. Lead was the major metal of concern which poses health risk to adults and children through ingestion of soil and dust. Hazard Index value for Pb and Cu from exposure to contaminated dust in adults was 0.73 and 0.57, respectively. Adults were found to have the life time risk of cancer from exposure to Cr (3.4E-03) in contaminated soil.